Kemiskinan Masyarakat Nelayan Ditinjau dari Segi Budidaya di Desa Raja Bejamu Kecamatan Sinaboi Kabupaten Rokan Hilir Provinsi Riau - Supriadi Supriadi; Firman Nugroho; Viktor Amrifo (Berkala Perikanan Terubuk, 2016)
This research was conducted in January 2016 on the Raja Bejamu Village Sinaboi District, Rokan Hilir Regency, Riau Province. The purpose of this research are: 1) To determine the looked of fishing communities in the Raja Bejamu Village the working spirit/ work 2) Fisherman community perspective of poverty in the Raja Bejamu Village against poverty 3) To know the state of poverty of fishing communities in the Raja Bejamu Village. The method used in this research is qualitative and quantitative methods are supported, with 10 informants composed of village officials, ninik mamak and youth. Results from this research that the working spirit is important for people fishing Raja Bejamu Village for work as praying and poverty is a gift from God that must still be lived as it does not disturbing with other people's lives as well as their cultural factors that cause poverty in the Raja Bejamu Village namely by relax in the coffee shop while gambling.